Optimization Strategies of Na3V2(PO4)3 Cathode Materials for Sodium-Ion Batteries - Hu, Jiawen; Li, Xinwei; Liang, Qianqian; Xu, Li; Ding, Changsheng; Liu, Yu; Gao, Yanfeng (Nano-Micro Letters, 2024)
Na3V2(PO4)3 (NVP) has garnered great attentions as a prospective cathode material for sodium-ion batteries (SIBs) by virtue of its decent theoretical capacity, superior ion conductivity and high structural stability. However, the inherently poor electronic conductivity and sluggish sodium-ion diffusion kinetics of NVP material give rise to inferior rate performance and unsatisfactory energy density, which strictly confine its further application in SIBs. Thus, it is of significance to boost the sodium storage performance of NVP cathode material. Up to now, many methods have been developed to optimize the electrochemical performance of NVP cathode material. In this review, the latest advances in optimization strategies for improving the electrochemical performance of NVP cathode material are well summarized and discussed, including carbon coating or modification, foreign-ion doping or substitution and nanostructure and morphology design. The foreign-ion doping or substitution is highlighted, involving Na, V, and PO43− sites, which include single-site doping, multiple-site doping, single-ion doping, multiple-ion doping and so on. Furthermore, the challenges and prospects of high-performance NVP cathode material are also put forward. It is believed that this review can provide a useful reference for designing and developing high-performance NVP cathode material toward the large-scale application in SIBs. Highlights: 1 Optimization strategies for high-performance Na3V2(PO4)3 (NVP) cathode material are well summarized and discussed, including carbon coating or modification, foreign-ion doping or substitution and nanostructure and morphology design. 2 The foreign-ion doping or substitution is highlighted, involving the Na, V, and PO43− sites, which include single-site doping, multiple-site doping, single-ion doping and multiple-ion doping. 3 Challenges and future perspectives for high-performance NVP cathode material are presented.